Analysis of Operational Management Functions at SMPT Daarul Muttaqien Surabaya - Islamiyah, Nuril; Detasya, Annola; Tarigan, Ramli; Arthana, Nana; Dwiningwarni, Sayekti (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Education as a place for individual development, improving the quality of life and a symbol of innovative progress requires aspects that are used as measuring tools in creating optimal learning. This research aims to explain the operational management function at SMPT Daarul Muttaqien which consists of three parts, namely operational planning including capacity, location, layout, quality and methods, operational scheduling for setting service schedules and operational control in the form of a monitoring plan in the form of monitoring and controlling. with systems and tools. In this research, the method used is descriptive qualitative with secondary data collection using interview techniques and word-dominant quantitative data analysis by reviewing the collected data, summarizing, categorizing, examining, drawing conclusions and verifying. The results of the research show that Daarul Muttaqien SMPT needs improvements in capacity planning in considering the ratio of the number of students to the number of teachers and the less than optimal room capacity which makes some teachers teach more than one subject. Apart from that, planning methods were felt to be lacking because the foundation's public relations were not optimal in managing school information, resulting in less than optimal management of school social media. However, location planning, layout planning, quality planning, operational scheduling and operational control have gone quite well.